Dinámica de los bosques en territorios que transitan entre el conflicto y la construcción de paz: Un análisis espacial con enfoque territorial en municipios de Antioquia priorizados por el Acuerdo en Colombia - Gutiérrez Zapata, Diana Maria; Cerón Muñoz, Mario Fernando; Barahona Rosales, Rolando; Castro-Nuñez, Augusto Carlos; López-Camacho, Maribel; Rodríguez Espinosa, Holmes; Aguilar-Ávila, Jorge (Universidad Autónoma Chapingo, 2025)
This publication is the result of the doctoral research conducted by the first author as part of her PhD in Animal Sciences at the University of Antioquia. The study integrates multiple methodological approaches to analyze the factors driving deforestation—considering not only traditional biophysical and economic aspects but also human dimensions—at a local scale in municipalities prioritized under Colombia’s peace agreement.